Pajak Penghasilan (PPh) Pasal 22 - Siti Fatimah; Arya Advany (CV. ITTC INDONESIA, 2026)
Income Tax Article 22 is a strategic tool used to collect tax in advance on certain transactions, such as imports and government procurement. This study aims to analyse the concept, mechanism, role, challenges, and impact of Income Tax Article 22 on taxpayer compliance. The research employs a descriptive qualitative approach based on regulations and related literature. The findings demonstrate that Income Tax Article 22 contributes to increasing state revenue and formal taxpayer compliance. To maximise its efficacy, however, legislative simplicity and technology advancement are required because its implementation still faces obstacles including complicated tariffs and inadequate digital systems.